NO-DO as an anchor of local cultural identities: The image of the artistic and monumental legacy of Murcia in the oficial cinematography of the Franco regime - Aliaga Cárceles, José Javier (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
NO-DO played a major role in the interpretation of the Spanish territory (landscapes, customs, traditions, monuments, etc.) through its film productions during the Franco regime and the Transition. This article analyses the image and the identity that was forged of the artistic and monumental legacy of Murcia, from the methodology of visual studies. The conclusions demonstrate that while the cathedral and the urban view of Murcia shaped the image-brand of the city, as had already happened in the 19th century, the sculptors Salzillo and Planes were the main representatives of Murcian art in Franco’s official cinema.